Optical random Riemann waves in integrable turbulence - Stephane Randoux; Francois Gustave; Pierre Suret; Gennady El (2017)
We examine integrable turbulence (IT) in the framework of the defocusing cubic one-dimensional nonlinear Schrodinger equation. This is done theoretically and experimentally, by realizing an optical fiber experiment in which the defocusing Kerr nonlinearity strongly dominates linear dispersive effects. Using a dispersive-hydrodynamic approach, we show that the development of IT can be divided into two distinct stages, the initial, pre-breaking stage being described by a system of interacting random Riemann waves. We explain the low-tailed statistics of the wave intensity in IT and show that the Riemann invariants of the asymptotic nonlinear geometric optics system represent the observable quantities that provide new insight into statistical features of the initial stage of the IT development by exhibiting stationary probability density functions.